Математичнемоделювання якості підземних трубопроводів в умовах корозійної втоми - Юзевич, Лариса (Видавництво Львівської політехніки, 2016)
Розроблено рекомендації щодо оцінювання довговічності та якості підземних металевих трубопроводів в умовах втоми. Встановлено особливості раннього виявлення кризових (передаварійних) ситуацій. Розроблено методику розрахунку ризику в смузі проходження траси трубопроводу з урахуванням його технологічної специфіки і впливу місцевих чинників різної природи на можливість розвитку аварії. Разработаны рекомендации относительно повышения качества математических моделей мониторинга сложных объектов техники с низким уровнем динамики процессов, которые характеризуются особенностями раннего выявления кризисных (предаварийных) ситуаций. The presence of fatigue cracks on the surface of metallic underground pipelines sharpens the problem of calculation values of strength characteristics at the action of corrosive environments, that did not find the complete decision nowadays. In this connection it is needed to correct the row of defects and normative and technical documents related to insufficient actuality of corresponding. In normative documents from exploitation of construction elements on this time the reasonable norms of legitimate values of corrosive damages, reduction of bearing strength of construction elements are absent. It creates complications in the ground of normative terms of exploitation and evaluation of the maximum state of metallic constructions, in planning of charges on exploitation of construction elements and repair and restoration work. An object of researches is underground metallic pipelines that are in the conditions of corrosion-fatigue destruction. The subject of a study is normative document. It is expedient to specify and perfect on the basis of the information got on results monitoring of functioning of underground metallic pipelines. Aim of this article – formulation of criteria and scientifically reasonable recommendations for providing of quality of underground metallic pipelines exploitation in the conditions of fatigue and influence of aggressive environment, and also forming of normative principles in sphere of pipeline transport. Only underground main gas pipelines in the ground electrolyte in the conditions of low cycle fatigue should be considered. For the improvement of normative documents it is expedient to build a complex mathematical model, that will unite the physical and chemical model of corrosion-fatigue processes, model of piling up description of damages in metals and elements theory of risks. For the modeling of speed increasing of fatigue crack on the middle rectilineal area of kinetic curve equation that binds length of fatigue corrosive crack and amount of cycles of loading to the coefficient of intensity of mechanical tensions is used. Corresponding equation is improved for a metal in corrosive environment and the pH-value of environment, and also electrode potential of metal, is here taken into account. For the base model of damage accumulation for metals in the conditions of irregular deformation a model that is based on the curvilinear change of damages, and power going is used near description of process of low cycle fatigue, that is a base on criterion of fatigue strength of V. T. Troschenko. Critical specific work that answers the origin of fatigue crack is included in a criterion. For description of the irregular cyclic loading of metal expression, power descriptions of metal and function of relative value of amplitude intensity of tensions, that characterizes the degree of mechanism influence of fatigue on the fatigue curve is also used. Evolutional equation is written in for the modeling of low cycle fatigue of metals. Lviv Polytechnic National University Institutional Repository http://ena.lp.edu.ua Вимірювальна техніка та метрологія, №77, 2016 р. 137 Correlation for description of low cycle corrosion fatigue of material in metallic underground pipelines is complemented by equations for the evaluation of risks within the limits of investment project that executes corresponding organization (enterprise). For optimization of informative streams of enterprise and improvement of the defence system of metallic underground pipelines from a corrosive fatigue the quality functional is used taking a feed-back in methodology of risk evaluation of investment project into account. The aim of that application is the improvement of the corresponding normative and technical providing. In zones with non-stationary plasticity strain it is expedient to use the criteria of adhesion strength, biocorrosive aggressiveness of soils, mechanical criterion for the coefficient of intensity of tensions (the overstrain of corrosive process takes into account), the criterion of corrosive stability of pitting, criterion correlation for the evaluation of speed of stability corrosion of metal in the defect of isolating coverage together with entered by diagnostic weight of signs and diagnostic value of inspections, that will complement, will specify and will perfect the system of the corrosive monitoring of pipelines and able to be used for control of corrosive process. With their help optimization of terms of construction elements defence of oil and gas industry, that is described and regulated by a state standard, can be conducted. As a result a new complex mathematical model is offered in relation to upgrading of corrosion protection of metallic underground pipelines from positions of corrosion fatigue, electrochemistry, physics of surface processes, mechanics of destruction and theory of risks. The conducted modeling takes piling up of damages in metals into account and allows to study the mechanisms of distribution of corrosive fatigue cracks in underground metallic pipelines that are in aggressive environments, in particular, in saltwater and ground electrolyte. The results of mathematical modeling are the basis of methodology development and improvement of normative and technical documents for metallic underground pipelines, that are under the action of the regular and irregular cyclic loading in the conditions of low cycle corrosive fatigue. The joint use of corrosive fatigue criteria and corrosive monitoring criteria of pipelines offered in this article will allow in detail enough from positions of corrosive fatigue, electrochemistry, physics of surface processes, mechanics of destruction and theory of risks to study the mechanisms of distribution of corrosive fatigue cracks in underground metallic pipelines that are in aggressive environments.
Keywords: трубопровід; нормативно-технічна документація; малоциклова втома; якість; ризики; корозія; механічне навантаження; мониторинг; математическая модель; качество; сложный объект; диагностическая система; уровень динамики; техника; underground pipeline; metal; damage; cyclic loading; corrosion; low cycle fatigue; quality, risks; normative and technical documentation; 504.75:681.2.543